Comparison of direct and indirect pyrolysis of micro-algae Isochrysis. (March 2015) - Wang, Xin; Zhao, Bingwei; Tang, Xiaohan; Yang, Xiaoyi
Highlights: Indirect pyrolysis pathway has higher total oil yield. N -Heterocyclic compounds and phenols are high in defatted microalgae pyrolysis oil. Hydrocarbons content decreased in pyrolysis oil for defatted microalgae. C12–16 largely decrease and nearly no C17–22 in defatted microalgae pyrolysis oil. Oil yield simulation complies with Compounds Biofuel Model. Abstract: Yield and composition of pyrolysis oil in direct and indirect pyrolysis process were investigated which indicated that pyrolysis of defatted microalgae provided a potential way to convert protein and carbohydrate to biofuels. Defatted microalgae pyrolysis with lipid extraction has higher total oil yield than only microalgae direct pyrolysis. There was an increase for N -heterocyclic compounds and phenols and a decrease for hydrocarbons in defatted microalgae pyrolysis oil. There is an apparent decrease from C12 to C16 and nearly no carbon distribution from C17 to C22 for defatted microalgae pyrolysis. Based on composition of pyrolysis feedstock, pyrolysis oil yields were simulated by Compounds Biofuel Model and their accuracy was less than ±4.4%. Considering total oil yield and characteristics, microalgae pyrolysis after lipid extraction process is a promising way for microalgae utilization.